An Empirical Study with Function Point Analysis for Requirement Changes During Software Development Phase - Shah, Jalal; Kama, Nazri; Zahari, Amelia (International Journal of Engineering and Technology, 2018)
Software Requirement Changes (SRC) take place at any stage during the development of a software system. Allowing for too many changes may increase in price and period of the development of a software system. On the other hand, denying changes may increase consumer unhappiness. Software Change Effort Estimation (SCEE) is one of these techniques that can help software development team in accepting or rejecting a change. At present many SCEE techniques have been introduced and Function Point Analysis (FPA) is one of them. FPA commonly used for SCEE during the early phases of software development cycle. Our previous works have shown that it is a challenging task to implement FPA technique in Software Development Phase (SDP) due to the inconsistent states of software artifacts such as (1) some are fully developed, (2) some are partially and (3) some are not developed yet. Hence, an empirical study is conducted on FPA to analyze the capability of the FPA technique to support SCEE in the context of software development phase. From the study, we found that the FPA technique is not able to present the: (1) current state of software artifacts; and (2) impact of SRC on software artifacts. As a result, we recommended in our future works that the integration of FPA with Impact Analysis (IA) technique that can overcome the limitations and potentially giving higher accuracy of SCEE results.